Durability of biopolymeric composites formulated with fillers from a by‐product of coffee roasting. Issue 3 (30th December 2021) - Sisti, Laura; Totaro, Grazia; Rosato, Antonella; Bozzi Cionci, Nicole; Di Gioia, Diana; Barbieri, Luisa; Saccani, Andrea
Abstract: Particulate composites based on poly(lactic acid) (PLA) and poly(butylene succinate) (PBS) biopolymers have been formulated. Silver skin (SSK), the by‐product derived from the roasting of coffee beans, has been milled to micrometric size and added up to a 30 wt% of loading, without any previous treatment. The dynamic mechanical properties of the composites have been investigated, as well as the stability toward UV and IR radiation. The filler improves some mechanical properties such as the elastic modulus ( E ′) mostly in PBS. Photoaging experiments demonstrate that SSK, due to its polyphenols content and antioxidant activity, is able to protect both PLA and PBS from UV degradation, highlighting an added value of SSK waste‐based composites. Abstract : Biocomposites based on poly(lactic acid) (PLA) or poly(butylene succinate) (PBS) with silver skin (SSK), a by‐product derived from the roasting of coffee beans, have been formulated. SSK, due to its polyphenols content and antioxidant activity, is able to protect both PLA and PBS from UV degradation. This approach is effective in terms of waste valorization and decrease of polymeric‐based materials cost.